2013
DOI: 10.1248/cpb.c12-00500
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity and DNA-Binding Investigations of Isoeuxanthone and Its Piperidinyl Derivative

Abstract: The binding mode and affinity of isoeuxanthone (1,6-dihydroxyxanthone) (1) and its piperidinyl derivative (1-hydroxy-6-(2-(1-piperidinyl)ethoxy)xanthone) (2) with calf thymus DNA were studied using absorption spectroscopy, fluorescence spectroscopy, circular dichroism (CD) spectroscopy and viscosity measurements. Results indicate that the two xanthones can intercalate into the DNA base pairs by the plane of xanthone ring and the binding affinity of the piperidinylethoxy substituted xanthone 2 is stronger than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…By promoting S-phase arrest, these compounds impair DNA replication [24]. Consistently, previous evidence has indicated that xanthone derivatives may interact with DNA through intercalation, suppressing its replication in cancer cells [11,12].…”
Section: Xgac Induces Cell Cycle Arrest Apoptosis and Genotoxicity In...supporting
confidence: 66%
See 1 more Smart Citation
“…By promoting S-phase arrest, these compounds impair DNA replication [24]. Consistently, previous evidence has indicated that xanthone derivatives may interact with DNA through intercalation, suppressing its replication in cancer cells [11,12].…”
Section: Xgac Induces Cell Cycle Arrest Apoptosis and Genotoxicity In...supporting
confidence: 66%
“…Xanthones are O-heteroaromatic tricyclic scaffolds, which provide a wide range of derivatives with several biological responses, representing a privileged structure for anticancer drug development [10]. Particularly, this class of oxygen-containing heterocyclic compounds can intercalate into the base group pairs of DNA due to the appropriate planarity of the xanthone ring, causing DNA damage in cancer cells through non-covalent interaction with DNA [11,12]. In addition, the glycosidic moiety of natural glycosides of flavonoids and xanthones may exhibit biological activities that positively affect the antitumor activity [13].…”
Section: Introductionmentioning
confidence: 99%
“…33−36 The xanthone moiety, having similarity with the planar tricyclic aromatic scaffolds of anthracycline (e.g., doxorubicin), has also been shown to interact with dsDNA. 37,38 A few xanthone derivatives anchored with certain groups have been reported to show specificity toward G4 DNA over dsDNA, but their antiproliferative activities in cancer cells were found to be insignificant. 39−41 Recently, a report shed light on xanthone derivatives conjugated with aza-aromatic pendants as potent G4 DNA binders, including a comparison with the previously reported xanthone-based G4 binders.…”
mentioning
confidence: 99%
“…Secondary metabolites based on xanthones, which are diversely populated in nature, occur mainly in plants and fungi. These contain dibenzo-γ-pyrone frameworks and are known to exhibit different biological activities. , Due to the pharmacological importance of the xanthone derivatives, much attention has been paid toward the isolation of these compounds from natural products as well as the synthesis of new xanthone derivatives as potential drug candidates for antimicrobial, anti-inflammatory, antiviral, anti-cancer, antimalarial, antioxidant, anticonvulsant, and anti-HIV treatments. The xanthone moiety, having similarity with the planar tricyclic aromatic scaffolds of anthracycline (e.g., doxorubicin), has also been shown to interact with dsDNA. , A few xanthone derivatives anchored with certain groups have been reported to show specificity toward G4 DNA over dsDNA, but their anti-proliferative activities in cancer cells were found to be insignificant. Recently, a report shed light on xanthone derivatives conjugated with aza-aromatic pendants as potent G4 DNA binders, including a comparison with the previously reported xanthone-based G4 binders . However, there is significant scope to appropriately tailor the xanthone central core and side chains in order to increase the effectiveness of such compounds further, which could lead to selective G4 stabilization and pronounced cancer cell toxicity.…”
mentioning
confidence: 99%
“…14,15) The findings suggested that isoeuxanthone modulated with piperidinyl group exhibited more strong DNA-binding affinity and antitumor activity than isoeuxanthone itself. In our continued effort to develop anti-cancer drug candidates, a series of isoeuxanthone derivatives ( Fig.…”
mentioning
confidence: 99%